Democratic politics and cosmopolitanism in the last thought of Julio De Zan - De Miguel, Jorge (ARFIL y UNL, 2020)
The article deals with Julio De Zan’s last thought about philosophy of democracy and cosmopolitanism. Different visions such as the role of civil society, the legitimacy of political power, and democratic cosmopolitanism are considered with reference to contemporary civil society as the public space in which democratic power is built. De Zan’s ideas of a global political order not organized as a traditional state and supported in a Kantian ethical community receive a positive comment, along with his powerful invocation of a not substatialized sovereignty.